Study Of Antioxidant Aktivity, Anticolestrol And Antihypertence Of Extract Rusip - Rinto Rinto; Ace Baehaki; Hafif Subarka (Jurnal FishtecH, 2019)
The purpose of this research was to be know  antioxidant activity, anticolestrol and antihypertence of extract rusip. This research was conducted from May 2017 until October  2017 using experimental laboratory method and data analysis was done descriptively. The research stages included measurement of pH, salt content analysis, determination of protein content, determination of peptides, antioxidants testing with the ABTS method, the analysis of ACE inhibitors (Angiotensin Converting Enzyme) and analysis of HMG-CoA reductase inhibitors. The results showed  that there are three types of rusip which has the complete label is rusip A, B and C. The pH value rusip ranged from 5.85 to 6.01. The salt contained in rusip ranged from 13.94 to 15.68%. Rusip protein content ranged from 14.71 to 18.39 mg / mL. The content of yield rusip extract ranged from 2.26 to 3.32 % and the content of peptide extract ranged from 13.05 to 14.80%. Rusip is a highly protein-rich food and contains many peptides. The antioxidant activity of rusip extract and activity of HMG-CoA inhibitor of russip extract are low. Rusip extract has a high activity as an ACE inhibitor (Angiotensin-I Converting Enzyme) of 95.75%.